The Influence of Customer Perceived Value and Service Quality on Customer Loyalty through Complaint Handling : Case Study on PT Pimaimas Citra - Andi Wijanarko; Edi Sugiono; Rahayu Lestari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Motivated by the decline in consumer loyalty at PT Pimaimas Citra, this study aims to examine the partial influence of Customer Perceived Value, and Service Quality on Customer Loyalty, either directly or indirectly through the intervening Complaint Handling variable. The research approach is quantitative, with the research location at PT Pimaimas Citra, Jakarta. One-time research time, 2025. The primary data collection technique uses surveys, and the secondary data collection technique uses the desk study/desk research method. Inferential data analysis technique uses SEM-PLS. The results of the study show that Service Quality has a positive and significant effect on Complaint Handling, and has a negative and significant effect on Customer Loyalty. Complaint Handling has a positive and significant effect on Customer Loyalty. Complaint Handling plays a positive role in both the influence of Customer Perceived Value on Customer Loyalty; and the influence of Customer Loyalty on Customer Loyalty. Meanwhile, Customer Perceived Value has a positive but insignificant effect on Customer loyalty; and has a positive but not significant effect on Complaint Handle.